Monoclonal Antibodies Against Factor Viii Procoagulant Activity - Sultan, Y; Sola, B; Avner, Ph; Maisonneuve, P; Jeanneau, C (Thrombosis and Haemostasis, 1981)
Monoclonal antibodies against the factor VIII/Von Willebrand molecule were obtained using the hybridoma technique. Splenocytes of mice immunized with a commercial preparation of high purity antihemophilic factor were fiised with a non secreting myeloma cell line SP 2/0. Hybrid cells were cloned twice by limiting dilution. Among 8 antibodies reacting with purified F.VIII/VW factor in a solid phase radio immunoassay, two of them showed an inhibitory activity against the procoagulant activity of the antihemophilic factor. This inhibitory activity was not detected in culture supernatants. Presumably in corelation with subtances of the culture medium interfering with the coagulation process and masking the neutralizing activity. However the anti VIIIc activity was demonstrated in the ascitic fluid obtained from mice injected with hybridoma cells.The specific anti VIIIc neutralizing activity of F4 115 monoclonal antibody is dependent on Ig concentration, time of incubation, temperature and Ph. In contrast with most of anti VIIIc inhibitors occuring in multitransfured hemophiliac, neutralization was more rapid and highier at 4° than 37°C. This neutralizing activity is absorbed by normal plasma or purified F.VIII preparation, however it is not absorbed by plasmas of a limited number of severe hemophilic and severe Von Willebrand patients. The study of a larger patients population is in progress.The second antibody F4 415 showed different inhibitory properties. Inhibition of the procoagulant activity is independent of incubation time butdependent on temperature and similarly more active at 4°C.These monoclonal antibodies provide new tools to investigate the procoagulant piece of the F.VIII molecule